The classification of real singularities using Singular. Part II: The structure of the equivalence classes of the unimodal singularities. (May 2016) - Marais, Magdaleen S.; Steenpaß, Andreas
Abstract: In the classification of real singularities byArnold et al. (1985), normal forms, as representatives of equivalence classes under right equivalence, are not always uniquely determined. We describe the complete structure of the equivalence classes of the unimodal real singularities of corank 2. In other words, we explicitly answer the question which normal forms of different type are equivalent, and how a normal form can be transformed within the same equivalence class by changing the value of the parameter. This provides new theoretical insights into these singularities and has important consequences for their algorithmic classification.